Sedentary Behaviors and Biomarkers Among Breast Cancer Survivors - Hartman, Sheri J. (J Phys Act Health, 2017)
BACKGROUND: Sedentary behavior is associated with increased risk of poor outcomes in breast cancer survivors, but underlying mechanisms are not well understood. This pilot study explored associations between different aspects of sedentary behaviors (sitting, prolonged sitting, sit-to-stand transitions, and standing) and breast cancer risk-related biomarkers in breast cancer survivors (n = 30). METHODS: Sedentary behavior variables were objectively measured with thigh-worn activPALs. Breast cancer risk-related biomarkers assessed were C-reactive protein (CRP), insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) and were measured in fasting plasma samples. Linear regression models were used to investigate associations between sedentary behavior variables and biomarkers (log CRP, insulin, and HOMA-IR). RESULTS: Sit-to-stand transitions were significantly associated with insulin resistance biomarkers (P < .05). Specifically, each 10 additional sit-to-stand transitions per day was associated with a lower fasting insulin concentration (β = −5.52; 95% CI, −9.79 to −1.24) and a lower HOMA-IR value (β = −0.22; 95% CI, −0.42 to −0.03). Sit-to-stand transitions were not significantly associated with CRP concentration (P = .08). Total sitting time, long sitting bouts, and standing time were not significantly associated with CRP, insulin, or HOMA-IR (P > .05). CONCLUSIONS: Sit-to-stand transitions may be an intervention target for reducing insulin resistance in breast cancer survivors, which may have favorable downstream effects on cancer prognosis.